2023
DOI: 10.3390/mi14071450
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulosic Bionanomaterials for Biosensor Applications

Abstract: The rapid population growth, increasing global energy demand, climate change, and excessive use of fossil fuels have adversely affected environmental management and sustainability. Furthermore, the requirements for a safer ecology and environment have necessitated the use of renewable materials, thereby solving the problem of sustainability of resources. In this perspective, lignocellulosic biomass is an attractive natural resource because of its abundance, renewability, recyclability, and low cost. The ever-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 181 publications
(252 reference statements)
0
3
0
Order By: Relevance
“…It was reported that lignin-based polyurethanes doped with multiwall carbon nanotubes at concentrations above the percolation threshold are suitable for sensor applications [232]. The emerging developments in nanotechnology have led to exploring lignocellulosic bionanomaterials, specifically nanolignin, in developing highly sensitive biosensors [233]. For instance, in a study, gold bare electrodes were modified with organosolv and kraft lignin nanoparticles synthesized from sulfur-free and sulfur lignin, and the modified electrodes were assembled with concanavalin A and glucose oxidase for biosensing glucose.…”
Section: Prospects Of Lignocellulosementioning
confidence: 99%
“…It was reported that lignin-based polyurethanes doped with multiwall carbon nanotubes at concentrations above the percolation threshold are suitable for sensor applications [232]. The emerging developments in nanotechnology have led to exploring lignocellulosic bionanomaterials, specifically nanolignin, in developing highly sensitive biosensors [233]. For instance, in a study, gold bare electrodes were modified with organosolv and kraft lignin nanoparticles synthesized from sulfur-free and sulfur lignin, and the modified electrodes were assembled with concanavalin A and glucose oxidase for biosensing glucose.…”
Section: Prospects Of Lignocellulosementioning
confidence: 99%
“…The study by Durmaz et al [11] provides a comprehensive overview of the utilization of lignocellulosic bionanomaterials in biosensor applications, addressing the pressing need for sustainable solutions in response to challenges such as rapid population growth, energy demand, and climate change. Lignocellulosic biomass, prized for its abundance, renewability, and cost-effectiveness, offers a compelling alternative for sensor fabrication in various fields, including electronics, communication, biomedical, and tissue engineering.…”
mentioning
confidence: 99%
“…The authors highlight the remarkable properties of lignocellulosic bionanomaterials, such as biodegradability, biocompatibility, and enhanced electrical and thermal conductivity, making them ideal candidates for developing high-impact biosensors. By reviewing current developments and identifying challenges and opportunities, the article underscores the potential of lignocellulosic bionanomaterials to revolutionize biosensor technology and contribute to environmental sustainability [11].…”
mentioning
confidence: 99%